Analisis Persediaan Bahan Baku Plastik PET Bening dengan Metode Min-Max di PT Gajah Surya Plastik - Nadya Novianti Ramadhani; Tranggono (Jurnal Serambi Engineering, 2025)
The uncertain amount of raw materials greatly affects the smoothness of production in a company and the amount of production output, thus encouraging researchers to conduct research on raw material inventory control. PT. Gajah Surya Plastik, is a company engaged in plastic recycling. Companies need to know the minimum stock of raw materials that must be held and the maximum stock limit that the company can hold in order for the raw material supply to be optimal. The min-max stock method was used to determine the maximum and minimum stock levels of the company's clear PET plastic raw materials. This research was carried out using primary data on the company's raw materials and interviews with related parties. From the research, the results of the data processing are that the minimum stock limit is 38,254 kg and the maximum raw material stock limit is 67,309 kg. With a safety stock value of 9199 kg. In addition, the raw material consumption for the next period is forecast with minimum error using the exponential smoothing method. The results of this research minimise the occurrence of stockouts and overstocks of clear PET plastic raw materials, so that production runs optimally.